Influential Financial Planners and Islamic Financial Planning: A Social Media-Based Content Analysis - Amalia, Putri Syifa; Yunanda, Rochania Ayu; Mustafa, Mutya Qurratu’ayuni (Tazkia Islamic Finance and Business Review, 2024)
Financial planning has been increasingly significant where income levels are rising, the financial industry is becoming more complicated and financial products are becoming more complex. With higher income levels and fund excesses, people demand financial assistance services to manage their financial matters. The activities of financial planners continue to grow in line with the varying demand of customers. Conventional financial planning had developed during the 1970s, while the Islamic financial industry had just emerged. From an Islamic perspective, a financial planning framework would require Shariah-compliant products and services and a deep understanding of Islamic values and principles governing economic activities. This study aims to understand to what extent Islamic financial planning has been communicated and shared by financial planners/advisors and to understand their preferences and financial priorities in providing financial advice. This qualitative paper explores the social media of chosen financial planners and Islamic financial planners. Financial planners share their thoughts and ideas on their social media. Several influential financial planners were selected through some stages. Understanding their social media content will provide a picture of their financial planning. Discussion of Islamic financial planning is scant. The paper explores and offers a novel approach of whether financial planners and so-called Islamic financial planners have different financial planning. Using the particular framework of Islamic financial planning, Islamic financial planners are expected to have different financial planning emphasizing Islamic values and principles.